Technical Leadership of Virtual and Remotely Distributed Teams. Issue 1 (20th September 2021) - Dazzi, Francesco; McKelvin, Mark; Gallego, Elena; McCoy, Sean; Keen, W. Patrick; Weigel, Allison; Ziliox, Lisa
Abstract: The world is increasingly virtual and complex, with many relationships and teams at a global scale. The situation will not be changing any time soon. Sometimes, it is only possible to interact at a distance, of not only time zones and space, but also sometimes interpersonal distance, where names and voices make up another person. Regardless, technical teams will need good leadership to address complex situations in these virtual and remotely distributed (VaRD) environments. So, in a VaRD environment, do leadership practices and skills have to change? Do the tools, techniques, and technology make current practices for leadership in general, and the application of those practices obsolete? Maybe not. This paper seeks to examine the nature of what is really changing when leading in a VaRD environment through the lens of engineers leading teams in global and complex technical challenges. Those perspectives are analyzed to determine the factors that go into a VaRD environment. In addition, this paper analyzes how interactions between teams compare to an in‐person environment, how leadership practices are applied in this environment, and how technical leadership is tailored for these new environments.